Odpowiedź :
Odpowiedź:
a) 3 ( x-2) +4 ( x-2)= 3x - 6 +4x -8= 7x - 14
b) 8 ( x+4) - 5 ( x+4)= 8x +32 -5x -20= 3x +12
c) 3 ( x²-7) + 8 ( x²-7)= 3x²-21 +8x²-56= 11x²-77
d) 7 ( x-3) - ( x-3)= 7x -21 -x +3= 6x -18
e) 4 (x+5) +20 ( x+5)= 4x +20 +20x +100= 24x + 120
f) 0,2 (- 10 +x) - ( x-10)= -2 +0,2x -x +10= -0,8x +8
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
3(x - 2) + 4(x - 2) = 3x - 6 + 4x - 8 = 7x - 14
b)
8(x + 4) - 5(x + 4) = (x + 4) (8 - 5) = 3(x + 4) = 3x + 12
c)
3(x² - 7) + 8(x² - 7) = (x² - 7)(3 + 8) = 11(x² - 7) = 11x² - 77
d)
7(x - 3) - (x - 3) = (x - 3)(7 - 1) = 6(x - 3) = 6x - 18
e)
4(x + 5) + 20(x + 5) = (x + 5)( 4 + 20) = 24(x + 5) = 24x + 120
f)
0,2(-10 + x) - (x - 10) = (x - 10)(0,2 - 1) = -0,8(x - 10) = -0,8x + 8
Szczegółowe wyjaśnienie: